Steps towards ceramic process scale-up: analysis of a laboratory process - Mortara, L.; Navarro, A.; Whatmore, Roger W.; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2004)
In this paper the first steps towards a scaling up of a ceramic process are described, using as case study a lab-scale process, in which PZT ceramics are produced via an aqueous tape casting route. The process, the result of a feasibility study, was firstly analysed by drawing flowcharts; potential problems and flow bottlenecks were then identified and their solutions were pursued using a "soft" problem solving approach.